Functional Behavioral Assessments and Behavior Support Plans for Work-Based Learning. (May 2016) - Kittelman, Angus; Bromley, Katherine Wagner; Mazzotti, Valerie L.
Work experiences are linked to positive post-school outcomes for youth and young adults with disabilities. Unfortunately, students who struggle to manage conflict and challenges in work settings have a difficult time maintaining employment. Though ecological assessments are used to create supported work plans surrounding socially inappropriate behavior, some students may benefit from a more targeted function-based approach to addressing these behaviors in work settings. This article provides information about how functional behavioral assessments and behavior support plans, tools routinely used in schools, can be adapted for use in employment settings.